Exploring cognitive impairments and the efficacy of phosphatidylcholine and computer-assisted cognitive training in post-acute COVID-19 and post-acute COVID-19 Vaccination Syndrome - Hotz, Julian Frederic; Kellerberger, Sophie; Elea Jöchlinger, Sara; Danielova, Iren; Temizsoy, Hanife; Ötsch, Sandra; Goller, Jürgen; Yacob, Muhammad; Zifko, Udo (Frontiers in Neurology, 2024)
Purpose The COVID-19 pandemic has led to millions of confirmed cases worldwide, resulting in numerous deaths and hospitalizations. Long-term symptoms after infection or vaccination, known as Post-acute COVID-19 Syndrome (PACS) or Post-acute COVID-19 Vaccination Syndrome (PACVS), present a challenge for the healthcare system. Among the various neurological symptoms, cognitive impairments are frequently observed in PACS/PACVS patients. This study aimed to understand cognitive deficits in PACS/PACVS patients and evaluated potential treatment options, including phosphatidylcholine and computer-assisted cognitive training (CCT). Methods The Neuro-COVID Outpatient Clinic at Evangelic Hospital Vienna evaluated n = 29 PACS/PACVS patients from May 2023 to October 2023. Enrolled patients were divided into three therapy schemes: Group A received phosphatidylcholine, B received phosphatidylcholine plus access to a computer-assisted cognitive training program, and C (divided into two subgroups) served as a control group. Cognitive impairments were evaluated in multiple assessments (initial and during therapy) using the COGBAT test. Simultaneously, an assessment of the quality of life was conducted using the WHOQOL-BREF. Results Primary cognitive impairments, especially attentional deficits were notably evident compared to the general population. While all treatment groups showed cognitive improvement (significant or with a positive trend, but without reaching the level of statistical significance) after therapy, no significant interaction was found between assessment time points and treatment schemes for overall cognitive performance, attention, memory, and executive functions, suggesting consistency across the groups. The WHOQOL-BREF primarily demonstrated deficits in the domains of physical health and psychological well-being. Conclusion This study examined the impact of PACS/PACVS on cognitive performance and evaluated phosphatidylcholine and CCT as potential treatment options. Patients with PACS/PACVS showed notable cognitive deficits, especially in the domain attention. While the effectiveness of phosphatidylcholine and CCT in treating cognitive deficits was inconclusive, the study indicated the possibility of spontaneous remission of cognitive deficits in PACS/PACVS.